Joint Effect of Carotid Plaque and C-Reactive Protein on First-Ever Ischemic Stroke and Myocardial Infarction? - Eltoft, Agnethe; Arntzen, Kjell Arne; Wilsgaard, Tom; Hansen, John-Bjarne; Mathiesen, Ellisiv B.; Johnsen, Stein Harald (Journal of the American Heart Association, 2018)
Source at: http://doi.org/10.1161/JAHA.118.008951 Background: The joint effect of atherosclerosis and CRP (C-reactive protein) on risk of ischemic stroke (IS) and myocardial infarction (MI) has been sparsely studied. The aim of this study was to explore whether CRP mediates the risk of events in subjects with prevalent carotid plaque, examine synergism, and test whether CRP and carotid plaque add to risk prediction beyond traditional risk factors. Methods and Results: CRP and carotid total plaque area (TPA) were measured in 10 109 participants in the Tromsø Study from 1994 to 2008. Incident IS (n=671) and MI (n=1079) were registered until December 31, 2013. We calculated hazard ratios (HRs) of MI and IS according to categories of CRP (<1, 1–3, and >3 mg/L) and plaque status (no plaque and TPA below and above median) in Cox proportional hazard models with time-varying covariates. Multivariable-adjusted CRP >3 versus <1 mg/L was associated with risk of IS (HR, 1.84; 95% confidence interval, 1.49–2.26) and MI (HR, 1.46; 95% confidence interval, 1.23–1.73). TPA above median versus no plaque was associated with risk for IS (HR, 1.65; 95% confidence interval, 1.36–2.01) and MI (HR, 1.64; 95% confidence interval, 1.41–1.92). In participants with plaque, adjustment for CRP minimally attenuated the risk estimates. The highest incidence rates for MI and IS were seen in the group with both CRP >3 mg/L and TPA is above the median. TPA and CRP combined added to risk prediction beyond traditional risk factors. Conclusions: The simultaneous presence of subclinical atherosclerosis and elevated CRP was associated with increased risk of IS and MI. The combined assessment of subclinical atherosclerosis and inflammatory biomarkers may improve cardiovascular disease risk stratification.